How video works - Weise, Marcus (Focal Press, 2007)
How Video Works has been a bible for professionals in the video world since 1985. It offers easy to understand explanations of the entire world of video. A complete guide from analog video to all the new digital technologies, including HD, compression, and encoding. This book is a must-have for any broadcast or video production department. It is also perfect for the new video technician or non-tech creative professional who is just beginning to discover the digital world. Update your library with the brand new version of an industry standard.